The costs of the gig economy : musical entrepreneurs and the cultural politics of inequality in northeastern Brazil - Enriquez, Falina, 1983- (University of Illinois Press, 2022)
"Institutions in Recife, Brazil, have withdrawn subsidies in favor of encouraging musicians to become more entrepreneurial. Falina Enriquez explores how contemporary and traditional musicians in the fabled musical city have negotiated these intensified neoliberal cultural policies and economic uncertainties. Drawing on years of fieldwork, Enriquez shows how forcing artists to adopt "neutral" market solutions in fact reinforces, and generates, overlapping racial and class-based inequalities. Lacking the social and financial resources of their middle-class peers, working-class musicians find it difficult to uphold institutional goals of connecting the city's cultural roots to global markets and consumers. Enriquez also links the artists' situation to that of cultural and creative workers around the world. As she shows, musical sponsorship in Recife and the contemporary gig economy elsewhere employ processes that, far from being neutral, reflect governmental and corporate ideologies. Rich and vibrant, The Costs of the Gig Economy offers a rare English-language portrait of the changing musical culture in Recife"--